Egg cases of Bathyraja cousseauae, a poorly known large softnose skate from the Southwest Atlantic Ocean - Diego Martín Vazquez (2018)
The Joined-fins skate Bathyraja cousseauae (Chondrichthyes: Arhynchobatidae) has recently been described by Díaz de Astarloa & Mabragaña (2004) from the Southwestern Atlantic Ocean (SWA), and was also recorded in the Southeast Pacific. Currently, it is assessed as Near Threatened by the IUCN and crucial information about life history and reproduction is scarce. The genus Bathyraja is represented in the SWA by 11 species, most of them exploited as by-catch or target species. From these, egg cases of six species have been described so far. Here, we describe the egg case of B. cousseauae. A mature female bearing egg cases (total length: 1210 mm; disc width: 810 mm) was caught in April 2016 by bottom trawl at 54°14?2.4?S; 63°11?38.4? W, at 293 m depth. One egg case was found in each uterus. Thirteen morphometric characteristics were recorded. Egg cases were large, 127.8-128.2 mm total length (Lec, excluding horns), with maximum egg case width (Wmax) ~ 64 % of Lec. Lateral keel was relatively wide, about 9.5% of Wmax. Anterior apron was considerably narrower (6.7?8.4 times) than posterior apron. Posterior horns were similar in size than the anterior ones. Anterior respiratory canals were relatively large, slightly longer (1.4-1.7 times) than posterior ones. Egg cases in fresh were uniformly bright golden, covered totally by a dense layer of sticky woven-like fibres. Surface had longitudinal striations with abundant, sharp and tall prickles well arranged giving a velvety texture to the touch. Prickles were smaller in the central zone and posterior horns. Attachment fibres were observed at the bases of anterior and posterior horns. An accurate species-level identification of egg cases is crucial for recognizing nursery grounds. The larger egg cases from bathyrajids of the SWA described so far correspond to B. griseocauda and B. cousseauae. They can be distinguised each other by their case surface, being smooth to touch in the first one. The remaining species have smaller egg cases than the joined-fins skate.